Leiomyoma of the ureter in a child (The youngest reported case) (Case report) - Çobano?lu, Bengü; Özercan, Ibrahim H.; Yalçin, Orhan; Ergin, Ertürk (My University, 2004)
[Abstract Not Available]
Keywords: Leiomyoma; Ureteral neoplasm